Russia and the illicit arms trade - Berryman, John (Crime, law and social change, 2000)
Since the disintegration of the Soviet military industrial complex, the prospect of conventional arms and nuclear, chemical and biological weapons of mass destruction and their ingredients finding their way from Russia into other hands has become a matter of concern for both the Russian Federation and the international community. This article explores the scale, forms and consequences of illicit transfers of conventional arms and weapons of mass destruction and their ingredients from the Russian Federation into the international community. Russian military and security forces seem to have been the main sources of a wide range of illicit conventional arms, whether as a consequence of the participation of Russian armed forces in regional conflicts or as a consequence of the sale of equipment by corrupt officers, the covert commercial export by Russian arms manufacturers being largely confined to small arms and light weapons. The illegal diversion of nuclear, chemical and biological materials from the Russian Federation seems to have been less than was at one time feared but Western cooperation with the Russian Federation to reinforce existing nonproliferation regimes remains a high priority.